Diplodiosis : cytotoxicity and ultrastructural changes induced by diplodiatoxin, dipmatol and diplonine, toxic metabolites isolated from Stenocarpella maydis - Botha, Catherine Frances (University of Pretoria, 2015)
Thesis (PhD)--University of Pretoria, 2014.